The improvement of partnership of family and school – in the light of evaluation research - BIDZIŃSKI, KAROL (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Karol Bidziński, The improvement of partnership of family and school – in the light of evaluation research. Interdisciplinary Contexts of Special Pedagogy, no. 25, Poznań 2019. Pp. 197-227. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2019.25.09 Humanistically oriented, qualitative educational studies allow learning about and supporting the processes of social change, including the development of schools directed towards the implementation of the idea of inclusive education. Evaluation research seems to be particularly useful for achieving this goal. The results presented in the article are a part of the extensive material collected in field research, which was conducted in the years 2015-2018 in eight schools of Świętokrzyskie Voivodeship. The aim of the study was to describe school community activity and the subjective and intersubjective structure of the meaning of entities creating space for the implementation of students’ educational needs. The article presents the beliefs of parents and teachers on the educational partnership of schools and family, as well as barriers in its development, reconstructed on the basis of data originated from group discussions conducted in one of the schools that participated in the research.